ANALISIS PEMASARAN UDANG PUTIH (Litopenaeus vannamei) DI KELURAHAN KUALA SAMBOJA KECAMATAN SAMBOJA KABUPATEN KUTAI KARTANEGARA - Leni Faizah; Nurul Ovia Oktawati; Fitriyana (Jurnal Pembangunan Perikanan dan Agribisnis, 2021)
This research was aimed to determine the marketing channels, costs, margins, and farmer's share of white shrimp (Litopenaeus vannamei) in Kuala Samboja Village, Samboja Sub-district, Kutai Kartanegara Regency. The research was conducted in Kuala Samboja Village, Samboja Sub-district, Kutai Kartanegara Regency. The samples used in the study were 15 fishermen and 2 white shrimp (Litopenaeus vannmei) traders. The sampling method used was purposive sampling and snowball sampling. The results showed that: there are 2 marketing channels for white shrimp (Litopenaeus vannamei), namely the level zero (0) marketing channel and the level two (2) marketing channel with 2 types; meanwhile the marketing costs at the level zero (0) marketing channel is Rp. 392/kg, at the level two (2) type 1 marketing channel is Rp. 3.043/kg, and at the level two (2) type 2 marketing channel is Rp. 2,487/kg. The total marketing margin is at level two (2) marketing channel with Rp. 67,500/kg and Rp. 36,700/kg. And the highest farmer's share is at the zero level marketing channel (0) which is equal to 100% and is the most efficient marketing channel. Keywords: Marketing Channels, Costs, Margins, Farmer's Share, Kuala Samboja